2001
DOI: 10.1177/089875640101800101
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic Features of the Root Canal System of the Maxillary Fourth Premolar and the Mandibular First Molar in Dogs

Abstract: Root canal morphology was evaluated in 72 maxillary fourth premolar and 59 mandibular first molar teeth. An apical delta was present in all roots (n = 334). The apical delta represented approximately 12-18% of the total root length for all roots. Non-apical ramifications from the main canal were observed in 25.1% of roots. Secondary canal(s) were present in 20.6% of roots, while lateral canal(s) were present in 6.9% of roots. The distal root of the maxillary fourth premolar had the highest incidence (47.2%) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
28
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 10 publications
7
28
1
Order By: Relevance
“…In fully formed dog teeth there is normally an apical delta rather than an apical foramen providing a connection between the pulp and periodontal tissues. 36,38,48 In this study, apical deltas were demonstrated histologically in 86.4 % of the teeth examined. The neurovascular supply to the pulp of dog teeth passes through a variable number (from just a few to over 20) very narrow neurovascular canals, most of which are significantly less than 100-µm in width, and may extend to 3-mm or more from the apex.…”
Section: Histomicrographs From Different Teeth Showing Cystic Changesmentioning
confidence: 94%
“…In fully formed dog teeth there is normally an apical delta rather than an apical foramen providing a connection between the pulp and periodontal tissues. 36,38,48 In this study, apical deltas were demonstrated histologically in 86.4 % of the teeth examined. The neurovascular supply to the pulp of dog teeth passes through a variable number (from just a few to over 20) very narrow neurovascular canals, most of which are significantly less than 100-µm in width, and may extend to 3-mm or more from the apex.…”
Section: Histomicrographs From Different Teeth Showing Cystic Changesmentioning
confidence: 94%
“…However, these findings should be studied in a larger population to provide additional statistical verification of this observation. 4,28,29 In human teeth, bacteria may reach the periapical area from lateral canals and the wide apical foramen, whereas canine and feline teeth have an apical delta and fewer accessory canals (Fig.2). 24,26,27 Differences in anatomical characteristics between human, dog, and cat apices have been thoroughly studied.…”
Section: Apical Limits and Major Biologic Factors Influencing Outcomesmentioning
confidence: 99%
“…Together with the periodontal ligament, alveolar bone and gingivae, it contributes to the tooth support apparatus. [2][3][4][5][6][7] In dogs, carnassial and canine teeth are the most important teeth in regard to size and function. 1 Cementum thickness varies, being thicker at the apex and furcation regions and thinner at the cementoenamel junction.…”
Section: Introductionmentioning
confidence: 99%
“…The internal aspect of the cementum is juxtaposed with dentin, and with the dental pulp apically, whereas the external aspect interfaces with the periodontal ligament. 4,8,9 A more precise and complete knowledge of the topographic and microscopic anatomy of the root apex in dogs is needed. Cementum is formed at varying rates throughout life.…”
Section: Introductionmentioning
confidence: 99%